2004
DOI: 10.1088/0953-8984/16/49/009
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of pseudo-two-dimensional triangular antiferromagnets Ba3MSb2O9(M = Mn, Co, and Ni)

Abstract: The crystal structure and magnetic properties of 6H-perovskites Ba 3 MSb 2 O 9 (M = Mn, Co, and Ni) were investigated. The M = Co and Ni compounds have a hexagonal structure with space group P6 3 /mmc, while the Mn compound has a monoclinically distorted structure with space group C2/c. From the results of magnetic susceptibility and specific heat measurements, it was found that they show an antiferromagnetic transition at 10.0 K (for M = Mn), 3.8 K (Co) and 13.5 K (Ni), and the onset of the magnetic transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
106
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 28 publications
14
106
0
Order By: Relevance
“…Due to a strong spin-orbit coupling with a uniaxial crystal field, the ground state of Co 2+ ions is reduced to an effective spin-1/2 moment at temperatures below ∼ 250 K. 9,11 In the ab-plane these moments form a triangular lattice which are stacked directly on top of each other (space group P6 3 /mmc). The dominant magnetic coupling is attributed to the nearest-neighbor exchange interaction within the plane (J = 18 K), while the magnetic interlayer interaction (J ⊥ = 0.48 K) is known to be much smaller as the planes are separated by double layers of nonmagnetic Sb ions.…”
Section: 10mentioning
confidence: 99%
“…Due to a strong spin-orbit coupling with a uniaxial crystal field, the ground state of Co 2+ ions is reduced to an effective spin-1/2 moment at temperatures below ∼ 250 K. 9,11 In the ab-plane these moments form a triangular lattice which are stacked directly on top of each other (space group P6 3 /mmc). The dominant magnetic coupling is attributed to the nearest-neighbor exchange interaction within the plane (J = 18 K), while the magnetic interlayer interaction (J ⊥ = 0.48 K) is known to be much smaller as the planes are separated by double layers of nonmagnetic Sb ions.…”
Section: 10mentioning
confidence: 99%
“…Since the magnetic layers are separated by nonmagnetic layers consisting of the Sb 2 O 9 double octahedron and Ba 2+ ions, the intralayer exchange interaction is expected to be dominant. On the other hand, the antiferromagnetic ordering at the Néel temperature T N ≈ 3.8 K [18,20] is due to the weak interlayer exchange interaction. The DM interaction is absent in Ba 3 CoSb 2 O 9 because of the highly symmetric crystal structure with the space group P 6 3 /mmc.…”
mentioning
confidence: 99%
“…Magnetic Co 2+ ions form uniform triangular-lattice layers parallel to the ab-plane [19,20]. Since the magnetic layers are separated by nonmagnetic layers consisting of the Sb 2 O 9 double octahedron and Ba 2+ ions, the intralayer exchange interaction is expected to be dominant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16,18,19) In Ba 3 NiSb 2 O 9 , the uniform triangular lattice of magnetic ions is realized as in Ba 3 CoSb 2 O 9 . Indeed, recently it has been found that the magnetization curve of this compound also exhibits a clear 1/3 plateau.…”
mentioning
confidence: 99%